Dietary fiber alters immunity and intestinal barrier function of different breeds of growing pigs - Ding, Sujuan; Cheng, Yating; Azad, Md. Abul Kalam; Dong, Haibo; He, Jun; Huang, Pan; Kong, Xiangfeng (Frontiers in Immunology, 2023)
Dietary fiber (DF) regulates immune response and barrier function by interacting with epithelial cells and immune cells. However, the differences in the regulation of intestinal health of different pig breeds by DF remain obscure. Hence, a total of 60 healthy pigs (20 pigs/breed) from Taoyuan black (TB), Xiangcun black (XB), and Duroc (DR) pigs (body weight = 11.00 ± 1.00 kg) were fed two different levels (low and high) of DF for 28 days to evaluate the differences in the modulation of intestinal immunity and barrier function by DF in different pig breeds. The results showed that the TB and XB pigs had higher plasma Eos level, Eos%, and Lym% but lower Neu level compared with the DR pigs when fed low DF (LDF). The TB and XB pigs had higher plasma Eos, MCV, and MCH levels and Eos% while lower Neu% compared with the DR pigs when fed high DF (HDF). HDF decreased IgA, IgG, IgM, and sIgA concentrations in the ileal tissues of TB and XB pigs compared with the DR pigs, while the plasma IgG and IgM concentrations of TB pigs were higher than those of the DR pigs. Moreover, compared with the DR pigs, HDF decreased the levels of IL-1β, IL-17, and TGF-β in plasma, and IL-1β, IL-2, IL-6, IL-10, IL-17, IFN-γ, TGF-β, and TNF-α in the ileum of TB and XB pigs. However, DF did not affect the mRNA expression of cytokines in the ileum of TB, XB, and DR pigs, while HDF increased the TRAF6 expression of TB pigs compared with the DR pigs. In addition, HDF increased the Claudin abundance of TB and DR pigs compared with the pigs feeding with LDF. Moreover, in the LDF and HDF groups, the XB pigs had higher protein abundances of Claudin and ZO-1 compared with the TB and DR pigs. In conclusion, DF regulated the TB and DR pigs’ plasma immune cells, the XB pigs showed enhanced barrier function, and the DR pigs had increased ileal inflammation, which indicates that Chinese indigenous pigs are more DF tolerant than the DR pigs.